(untitled) (Cadernos de Sociomuseologia, 2017)
The present article has purpose to analyse clothes as important patrimony in the study of the relations of the man with society, the hierarchic and symbolic power exerted through the suits used for the priests during the liturgical celebrations and the importance of the intrinsic and attributed value of this object on the material culture. Using as research object parts of the collection ecclesiastical Suits of the Museum of the Suit of the Textile of the Foundation Feminine Institute of the Bahia. Keywords: liturgical cloth, Feminine Institute, hierarchy, communication and power.